Don’t Tap the Keg and Eight Other Essential Rules of Early Career Principals: An Editorial - Carolyn L. Carlson; Scott P. Myers (The Advocate, 2014)
Principals that are early in their careers have unique challenges to face in order to become successful in their administrative positions. Early career principals, future principals, and those who educate future principals in education administration programs at colleges and universities should be aware of these potential obstacles. This list of nine “essential rules” seeks to challenge new and future principals, as well as those who educate them, to consider some of the unique challenges faced as well as offer insight to effectively overcome them.